ANALISIS KEBIJAKAN PRASARANA, SARANA DAN UTILITAS (PSU) TERHADAP PERKEMBANGAN PERUMAHAN DI KABUPATEN JAYAPURA STUDY KASUS PERUMAHAN DJOKO INDAH - Dedi Julians Noya; Harmonis Rante; Petrus Bachtiar (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2022)
The PSU program in Joko Indah Housing is distributed in the 2018 and 2020 fiscal years for the construction of 120 environmental roads and 182 subsidized housing units. After the provision of this assistance, does it have a direct impact on the residents of the housing, especially the impact of socio-economic activities so that these impacts can affect the development of Joko Indah's housing. The objectives to be achieved in this study are to analyze the existing condition of road infrastructure, analyze the PSU Program policies impacting socio-economic activities and analyze the road infrastructure PSU Program policies affect the development. To achieve the objectives in this study, it was carried out using a quantitative research approach with factor analysis. The results of this study indicate that the existing road infrastructure in the Joko Indah Housing complex does not meet the criteria because it does not have sidewalks on road access or environmental roads. The element of accessibility in general is overall assessed by residents of housing Joko Indah agree that the existence of the PSU program in the form of road casting makes it easier for residents to access educational facilities, workplaces / places of business, health facilities, accessing markets or other economic activities, making it easier for other people outside Joko's housing. Indah to visit the housing, improve the quality of family education, increase family income, improve the quality of family health and improve interaction patterns with fellow residents of Joko Indah's housing. Based on the assessment by residents of the Joko Indah housing estate on the characteristics of the Joko Indah Housing Development, it can be summarized 3 main factors that form the basis of the assessment.